2018
DOI: 10.1021/acs.est.8b02805
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Computational Transcriptomics Reveals Novel Endocrine Disruptors in Largemouth Bass (Micropterus salmoides)

Abstract: In recent years, decreases in fish populations have been attributed, in part, to the effect of environmental chemicals on ovarian development. To understand the underlying molecular events we developed a dynamic model of ovary development linking gene transcription to key physiological end points, such as gonadosomatic index (GSI), plasma levels of estradiol (E2) and vitellogenin (VTG), in largemouth bass ( Micropterus salmoides). We were able to identify specific clusters of genes, which are affected at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…First, a dynamic model representing the development of healthy ovaries from unexposed fish was constructed, and the responses of the transcriptomes from fish collected from polluted areas were mapped to enable the identification of clusters of genes affected at different stages of ovarian development. Then, using a robust database that provides information on chemical interaction with genes, proteins, and diseases (Comparative Toxicogenomic Database), potential chemicals associated with specific molecular responses on the ovary were identified (155). Another study, applied the QSAR method utilizing chemical features and mode of action to predict acute toxicity effects of EDCs in fish.…”
Section: Qsar/structural Alertsmentioning
confidence: 99%
“…First, a dynamic model representing the development of healthy ovaries from unexposed fish was constructed, and the responses of the transcriptomes from fish collected from polluted areas were mapped to enable the identification of clusters of genes affected at different stages of ovarian development. Then, using a robust database that provides information on chemical interaction with genes, proteins, and diseases (Comparative Toxicogenomic Database), potential chemicals associated with specific molecular responses on the ovary were identified (155). Another study, applied the QSAR method utilizing chemical features and mode of action to predict acute toxicity effects of EDCs in fish.…”
Section: Qsar/structural Alertsmentioning
confidence: 99%
“…In Chinese hamster ovarian cells, QUR negatively affected the genetic stability of the cells, including chromosomal aberration and micronuclei (Carver et al, 1983; Engen et al, 2015). Using computational transcriptomics, the ovarian gene transcription, physiological endpoints, and endocrine disruptors (EDs) can be associated and QUR as an ED can perturb the development of largemouth bass ovary (Basili et al, 2018). Hence, it seems that QUR may have some negative effects on the special conditions and species.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…This model correlates gene transcription with key physiological end points and has been used to screen potential compounds that may disrupt the network. 16 Network-based analysis methods have also been successfully applied to placenta tissue. The results revealed that using the network-based transcriptome data analysis method to construct placental gene networks can elucidate the molecular mechanisms of fetal growth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly, another study has established a dynamic network model for ovarian development. This model correlates gene transcription with key physiological end points and has been used to screen potential compounds that may disrupt the network . Network-based analysis methods have also been successfully applied to placenta tissue.…”
Section: Introductionmentioning
confidence: 99%